Current Socio-pedagogical Approaches in Deviant Behaviour Prevention - Vilks, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The topicality of deviant behaviour prevention is related to the socio-economic crisis and its negative effects, which contribute expression increases of deflected social activities. Increase of poverty level determines the problem of public interest and the risk situation, which makes it necessary to improve the socio-pedagogical approach to deviant behaviorwarning. At the same time, social and pedagogical resources for constructive problem solving and deviant behaviour warning remainslimited. The increase of the efficiency of socio-educational activities is possible on the basis of relevant professional qualifications of employees, of the intervention of socio-educational impact (enhancing of the segment of activities).